2014
DOI: 10.1002/pbc.24928
|View full text |Cite
|
Sign up to set email alerts
|

The association between fasting hypoglycemia and methylated mercaptopurine metabolites in children with acute lymphoblastic leukemia

Abstract: High levels of 6MMP are associated with symptomatic hypoglycemia which may be mitigated by switching to morning or twice daily 6-MP dose administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 11 publications
(20 reference statements)
1
31
0
Order By: Relevance
“…Hypoglycemic episodes during fasting157160 have been associated with high levels of methylated 6MP metabolites 161. It can be counteracted by evening meals with slowly absorbed carbohydrates, by administration of rapidly absorbed carbohydrates (eg, apple juice) in case of symptoms, or by shifting to morning dosage.…”
Section: Toxicity and Relapse Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Hypoglycemic episodes during fasting157160 have been associated with high levels of methylated 6MP metabolites 161. It can be counteracted by evening meals with slowly absorbed carbohydrates, by administration of rapidly absorbed carbohydrates (eg, apple juice) in case of symptoms, or by shifting to morning dosage.…”
Section: Toxicity and Relapse Ratementioning
confidence: 99%
“…It can be counteracted by evening meals with slowly absorbed carbohydrates, by administration of rapidly absorbed carbohydrates (eg, apple juice) in case of symptoms, or by shifting to morning dosage. The latter reduces Ery-MeMP levels but the impact on relapse rate is unknown 161. Few patients develop symptoms of hypoglycemia such as severe nausea, itching, or malaise to a degree that requires dose reductions.…”
Section: Toxicity and Relapse Ratementioning
confidence: 99%
“…25,26 Interestingly, elevated levels of 6-MMPN was also associated with symptomatic hypoglycemia and switching from evening administration to morning administration decreases 6-MMPN while preserving 6-TGN levels. 27 How changing the timing of MP administration changes the metabolism 6-MP is not clear. Thus, further work on the mechanism of how allopurinol affects 6-MP metabolism is needed to better understand this effect to better incorporate this therapy into standard ALL treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Another scenario where allopurinol could be helpful is in patients with symptomatic hypoglycemia as allopurinol will lower 6-MMPN levels without having to change the timing of 6-MP administration. 27 However, 6-MMPN may also play a role in the antileukemic effect of MP by inhibiting de novo purine synthesis although allopurinol by itself also inhibits de novo purine synthesis. 28 Combination therapy with allopurinol needs to be incorporated into future clinical trials to ensure that long-term outcomes are not affected by this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The VDLD therapeutic regime that has been used clinically is the first-line approach for treatment of A-BLL. However, recent research has indicated an increase in the rate of resistance to chemotherapeutic drugs; in addition, these drugs impart severe toxic and side effects, thereby restricting the clinical use of this therapeutic regime (Brackett et al, 2014;Melachuri et al, 2014).…”
Section: Discussionmentioning
confidence: 99%